1964
DOI: 10.1039/tf9646000103
|View full text |Cite
|
Sign up to set email alerts
|

Gas-phase thermal decomposition of dimethyl mercury. Part 2.—The homogeneous reaction

Abstract: The homogeneous gas-phase pyrolysis of dimethyl mercury has been studied in a wide variety of conditions. The products and kinetic characteristics of the reaction are shown to be more complex than has been supposed. An abridged short-chain radical mechanism which accounts for the main features of the reaction is suggested. Evidence is presented which indicates that the initial unimolecular breakdown of dimethyl mercury is not in its first-order region in the usual range of pressures and temperatures employed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

1964
1964
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 3 publications
1
7
0
Order By: Relevance
“…The available high pressure Arrhenius parameters for the pyrolysis of dimethylmercury in the presence of suitable inhibitors are in reasonable agreement (1)(2)(3)(4). The results of Russell and Bernstein (I), k = 5.0 x 10" exp (-57 900/RT) s-', and of Kallend and Purnell (2), k = 5.0 x 101j exp (-57 600/RT) sC1 are in excellent agreement.…”
Section: Introductionsupporting
confidence: 71%
“…The available high pressure Arrhenius parameters for the pyrolysis of dimethylmercury in the presence of suitable inhibitors are in reasonable agreement (1)(2)(3)(4). The results of Russell and Bernstein (I), k = 5.0 x 10" exp (-57 900/RT) s-', and of Kallend and Purnell (2), k = 5.0 x 101j exp (-57 600/RT) sC1 are in excellent agreement.…”
Section: Introductionsupporting
confidence: 71%
“…It has been shown that benzophenone acts as a sensitizer for the cis-trans photoisomerization of the stilbenes.12,18 Benzophenone is among the group of compounds that are classified as "high-energy" sensitizers. 14 With such a sensitizer the mechanism of isomerization can be simplified to the following scheme in which T represents the triplet group that decays to groundstate molecules.18…”
Section: Resultsmentioning
confidence: 99%
“…Since the submission of this study for publication, a comprehensive study of the decomposition in the vicinity of 400°has been published by Kallend and Purnell. 14 Their proposed mechanism gives the rate equation = 2fci[DMM] + B[DMM]'A (13) where fci is the rate constant for the elementary reaction (CH,),Hg -CH3 + CH3Hg and B is a combination of several rate constants in their postulated mechanism. Their data are found to fit this expression rather well.…”
Section: Resultsmentioning
confidence: 99%